2016
DOI: 10.5194/angeo-34-279-2016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO<sub>2</sub> source and sink patterns over the Indian region

Abstract: Abstract. In this paper we examine CO 2 emission hot spots and sink regions over India as identified from global model simulations during the period 2000-2009. CO 2 emission hot spots overlap with locations of densely clustered thermal power plants, coal mines and other industrial and urban centres; CO 2 sink regions coincide with the locations of dense forest. Fossil fuel CO 2 emissions are compared with two bottom-up inventories: the Regional Emission inventories in ASia (REAS v1.11;2000 and the Emission Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Air masses over the Indian subcontinent were transported from the Indian Ocean region during summer (monsoon season) and from the inland during winter, therefore observations in Nainital are strongly affected by anthropogenic emissions from the Indo-Gangetic Plain during summer. Anthropogenic emissions, e.g., of CO 2 , in the Indo-Gangetic Plain are higher compared to other regions in India 9 caused by the dense concentration of industries (e.g., thermal power plants, steel plants, refineries) as well as by the very high population density in this area 27 . Thus air masses transported long-range from the south to Nainital, can uptake these emission while passing over the Indo-Gangetic Plain 9 .…”
Section: Resultsmentioning
confidence: 95%
“…Air masses over the Indian subcontinent were transported from the Indian Ocean region during summer (monsoon season) and from the inland during winter, therefore observations in Nainital are strongly affected by anthropogenic emissions from the Indo-Gangetic Plain during summer. Anthropogenic emissions, e.g., of CO 2 , in the Indo-Gangetic Plain are higher compared to other regions in India 9 caused by the dense concentration of industries (e.g., thermal power plants, steel plants, refineries) as well as by the very high population density in this area 27 . Thus air masses transported long-range from the south to Nainital, can uptake these emission while passing over the Indo-Gangetic Plain 9 .…”
Section: Resultsmentioning
confidence: 95%
“…These air masses can uptake polluted air while passing over the Indo-Gangetic Plain where anthropogenic emission are higher compared to other regions in India caused by the dense concentration of industries and the high population (e.g. Fadnavis et al, 2016). Therefore, the tracer for the Indian Ocean and the Bay of Bengal are included into the marker for the Asian monsoon air.…”
Section: Pommrich Et Al (2014))mentioning
confidence: 99%
“…The transportation reach contribute more to the increasing trend in southern part of basin which is to be studied whether anthropogenic or Natural network. Naik et al (2008) [19] reported that the weed spread area in the Chilika [21] reported the trend in CO 2 fluxes was −1.85 ± 2.3 %/year (TgC yr−1 ) in CT-2010, over Mahanadi basin.…”
Section: Review Of Literature:-mentioning
confidence: 99%
“…The fatality rate in the State prior to 2000 was even less than 10/annum, but it has increased at present. (OSDMA Report, GOO 2012) [21] in Orissa Fig 8( a). Lightening deaths 2277 in last seven years (SRC Odisha) and by first week of Aug-2017 no of deaths are recorded due to increased upper air cyclic circulations.…”
Section: Lightning:-mentioning
confidence: 99%